(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
PT X is a company engaged in trade with its main activity as a distributor of textile chemical products in the country. The laboratory division is one part of company activities that can pose a risk of accidents to the laboratory. In the last two years there has been an increase in the issue of work injury. The textile laboratory at PT X was built in order to support the company’s operations. The laboratory has several types of equipment whose main activities in the process often cause heat and noise, in which there is always a risk of injury such as electric shocks that cause burns, fires from boiler explosions, and contact with hazardous chemicals. The purpose of this study was to determine the potential risk value of work accidents in the laboratory environment. The hazard analysis process at PT X is not necessarily appropriate to the potential hazards in the work environment, therefore it is necessary to conduct an appropriate hazard analysis process to reduce or avoid hazardous risk actions. The purpose of this study is to determine the potential risk value of work accidents in this laboratory environment. This study uses the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method in identifying risks in the laboratory and the Fault Tree Analysis (FTA) method to determine the potential hazards by assuming if a failure occurs from a system. From these two methods the researcher uses Failure Mode and Effect Analysis (FMEA) to conduct an analysis that can provide recommendations for machine / process equipment maintenance in order to propose improvements to minimize the potential level of work accidents that occur. The results of this study indicate that if the risk level is found in the PT X laboratory and sources of danger from the Standard Operational Procedure (SOP). Risk priority number (RPN) indicates a high level of risk, researchers recommend routine maintenance of the fabric padder finishing machine, redesigning the machine layout, and the need for risk management in avoiding work accidents.